HUBUNGAN ANTARA PENGETAHUAN DASADARMA PRAMUKA DENGAN SIKAP YANG SESUAI NILAI PANCASILA SISWA KELAS V SEKOLAH DASAR DI KECAMATAN SETIABUDI - Ismaturrohmah; Zakiah, Linda; Sumantri, M. Syarif (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to determine the relationship between the knowledge of dasadarma scouts with attitudes that are by the values of Pancasila for fifth-grade elementary school students in the Setiabudi sub-district. This research uses a quantitative method with the correlational model. The subjects of this study were fifth-grade students at SDN Guntur 03 Pagi and SDN Menteng Atas 14 Setiabudi Subdistrict. The data in this study were collected through the dasadarma knowledge test and by filling out a questionnaire. The data analysis used is inferential statistics. The results are based on the correlation coefficient test r of 0.278 with a low correlation category level. In addition, the coefficient of determination test results obtained amounted to 7.75%. This shows that the attitude variable by the values of Pancasila by 7.75% is determined by the scout dasadarma knowledge variable. Thus, it can be concluded that the knowledge of dasadarma scout has a positive and significant relationship with attitudes that are by the values of Pancasila in fifth-grade elementary school students at SDN Guntur 03 Pagi and SDN Menteng Atas 14.